Cultivating social innovation for agri-food sustainability transformations: a literature review - Machteld Catharina Simoens; Caroline Hélène Dabard; Jonathan Friedrich; Juan Garzon; Felix Zoll (Journal of Rural Studies, 2026)

Unpacking pathways to a circular economy: A study of packaging innovations in Germany - Machteld Catharina Simoens (Sustainable Production and Consumption, 2024)

Can we talk? Disrupting science circles with narrative-led dialogs - Sina Leipold; Anran Luo; Machteld Simoens; Hanna Helander; Anna Petit-Boix (Environmental Science & Policy, 2024)

Lessons, narratives, and research directions for a sustainable circular economy - Sina Leipold; Anna Petit‐Boix; Anran Luo; Hanna Helander; Machteld Simoens; Weslynne S. Ashton; Callie W. Babbitt; Alba Bala; Catharina R. Bening; Morten Birkved; Fenna Blomsma; Casper Boks; et al. (Journal of Industrial Ecology, 2023)
The current enthusiasm for the circular economy (CE) offers a unique opportunity to advance the impact of research on sustainability transitions. Diverse interpretations of CE by scholars, however, produce partly opposing assessments of its potential benefits, which can hinder progress. Here, we synthesize policy‐relevant lessons and research directions for a sustainable CE and identify three narratives—optimist, reformist, and skeptical—that underpin the ambiguity in CE assessments. Based on 54 key CE scholars’ insights, we identify three research needs: the articulation and discussion of ontologically distinct CE narratives; bridging of technical, managerial, socio‐economic, environmental, and political CE perspectives; and critical assessment of opportunities and limits of CE science–policy interactions. Our findings offer practical guidance for scholars to engage reflexively with the rapid expansion of CE knowledge, identify and pursue high‐impact research directions, and communicate more effectively with practitioners and policymakers.

Discursive dynamics and lock-ins in socio-technical systems: an overview and a way forward - Machteld Catharina Simoens; Lea Fuenfschilling; Sina Leipold (Sustainability Science, 2022)
Understanding the dynamics of stability and change is key to accelerate sustainability transitions. This paper aims to advance and inspire sustainability transition research on this matter by collecting insights from interpretative environmental discourse literature. We develop a heuristic that identifies and describes core discursive elements and dynamics in a socio-technical system. In doing so, we show how the interplay of meta-, institutionalized, and alternative discourses, dominant, marginal, and radical narratives, as well as weak and strong discursive agency influence the socio-technical configuration. The heuristic suggests three discursive lock-ins reinforcing the stabilization of socio-technical systems: unchallenged values and assumptions, incumbents’ discursive agency, and narrative co-optation. Furthermore, it explores three pathways of discursive change: disruptive, dynamic and cross-sectoral. Overall, this paper puts forward a discursive perspective on sustainability transitions. It offers additional analytical approaches and concepts for discursive transition studies, elaborated insights on the dynamics within and between the analytical dimensions of a socio-technical system, as well as a theoretical baseline for analyzing discursive lock-in mechanisms and pathways of discursive change.